2021
DOI: 10.3390/ph14080711
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Studies on Nasal Formulations of Nanostructured Lipid Carriers (NLC) and Solid Lipid Nanoparticles (SLN)

Abstract: The nasal route has been used for many years for the local treatment of nasal diseases. More recently, this route has been gaining momentum, due to the possibility of targeting the central nervous system (CNS) from the nasal cavity, avoiding the blood−brain barrier (BBB). In this area, the use of lipid nanoparticles, such as nanostructured lipid carriers (NLC) and solid lipid nanoparticles (SLN), in nasal formulations has shown promising outcomes on a wide array of indications such as brain diseases, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 91 publications
(195 reference statements)
0
22
0
Order By: Relevance
“…In our study, to assess the cytotoxicity of silver nanoparticles, we used primary HNEpC cells, which are the most reliable two-dimensional in vitro model of the nasal epithelium [41]. We observed that the AgNPs were nontoxic to epithelial cells in concentrations that inhibited the growth of all bacterial isolates tested when incubated with the cells for 24 hours.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, to assess the cytotoxicity of silver nanoparticles, we used primary HNEpC cells, which are the most reliable two-dimensional in vitro model of the nasal epithelium [41]. We observed that the AgNPs were nontoxic to epithelial cells in concentrations that inhibited the growth of all bacterial isolates tested when incubated with the cells for 24 hours.…”
Section: Discussionmentioning
confidence: 99%
“…103,104,110 In recent years, due to the biodegradable and biocompatible characteristics, 111 SLN and NLC have shown potential success for several administration routes in medicine, such as for oral, [112][113][114][115] dermal, [116][117][118] parenteral, 119 ocular, 120,121 pulmonary, 122 and brain targeting. 7,[123][124][125][126] SLN and NLC applied to the skin can improve stability, drug targeting and penetration, and increase skin hydration compared with other drug nanocarriers. Therefore, they are considered as promising DDSs in treating skin disorders.…”
Section: Solid Lipid Nanoparticle and Nanostructured Lipid Carriersmentioning
confidence: 99%
“…Regarding their structure, suitable features for topical application include the drug-enriched shell nanoparticles, providing rapid drug release, which along with the occlusive effect is a favorable characteristic when increased drug penetration is necessary [288,293]. The disadvantages of SLNs, such as the tendency for drug expulsion or low drug loading capacity due to the ideal crystalline structure of the lipids, provide possibilities for further development, including the development of second-generation nanoparticles and structured lipid carriers (NLCs), which overcome the limitations mentioned above [284,294].…”
Section: Solid Lipid Nanoparticlesmentioning
confidence: 99%